2019
DOI: 10.3390/nano9020146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Six Carbon-Based Nanomaterials on the Rheological Properties of Nanofluids

Abstract: Nanofluids, dispersions of nanosized solid particles in liquids, have been conceived as thermally-improved heat transfer fluids from their conception. More recently, they have also been considered as alternative working fluids to improve the performance of direct absorption solar thermal collectors, even at low nanoadditive concentrations. Carbon-based nanomaterials have been breaking ground in both applications as nanoadditives during the last decade due to their high thermal conductivities and the huge trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 66 publications
(99 reference statements)
6
37
1
Order By: Relevance
“…Five different nanofluid sets, viz., CB/PEG400, nD87/PEG400, nD97/PEG400, G/D-p/PEG400 and G/D-r/PEG400, were prepared at 0.5 and 1.0% nanoparticle mass concentrations via a two-step method. Thus, the required amounts of nanopowder and base fluid necessary to obtain the predefined concentrations were weighted on an analytical balance Radwag AS 220/X (Radwag, Radom, Poland) with an accuracy of 1 × 10 −4 g. After mechanically shaking the mixtures using a Genius 3 (IKA, Staufen, Germany) vortex system for 30 min, samples were sonicated for 200 min in an Emmi 60 HC ultrasound wave bath (EMAG, Moerfelden-Walldorf, Germany) working with a ultrasound power of 450 W and a frequency of 45 kHz [81]. Special care was taken to periodically replace the water of the ultrasonic bath and avoid sample overheating during sonication process.…”
Section: Materials and Nanofluid Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Five different nanofluid sets, viz., CB/PEG400, nD87/PEG400, nD97/PEG400, G/D-p/PEG400 and G/D-r/PEG400, were prepared at 0.5 and 1.0% nanoparticle mass concentrations via a two-step method. Thus, the required amounts of nanopowder and base fluid necessary to obtain the predefined concentrations were weighted on an analytical balance Radwag AS 220/X (Radwag, Radom, Poland) with an accuracy of 1 × 10 −4 g. After mechanically shaking the mixtures using a Genius 3 (IKA, Staufen, Germany) vortex system for 30 min, samples were sonicated for 200 min in an Emmi 60 HC ultrasound wave bath (EMAG, Moerfelden-Walldorf, Germany) working with a ultrasound power of 450 W and a frequency of 45 kHz [81]. Special care was taken to periodically replace the water of the ultrasonic bath and avoid sample overheating during sonication process.…”
Section: Materials and Nanofluid Preparationmentioning
confidence: 99%
“…Pseudo-plastic viscosity curves were also reported by Marcos et al [71] when they studied the flow behavior of PEG400-based dispersions loaded with 0.05-1.0 wt.% of multi-walled carbon nanotubes.Żyła et al [83,92] comprehensively investigated the rheological behavior of ethylene glycol dispersions containing nano-diamond mixtures (nD87 and nD97 [92]) as well as graphite/diamond mixtures (G/D-p and G/D-r [83]), analyzing the effect that nano-diamond purity and ash content have on shear rate-shear viscosity curves, among other thermophysical properties. Recently, Vallejo et al [81] performed a complete rheological study of the dispersions of the same carbon-based nanomaterials used in the present study but based on ethylene glycol (EG). Vallejo et al [81] reported a shear-thinning behavior for suspensions of these five carbon nanopowders (CB, nD87, nD97, G/D-p or G/D-r) in the nanoparticle concentration range from 0.25 to 2.0%.…”
Section: Dynamic Viscositymentioning
confidence: 99%
“…The Laplace transform is applied to Equation (12) and the initial condition is used from Equation (8) to yield:…”
Section: Solution Of Momentum Equationmentioning
confidence: 99%
“…They found that the nanofluid behaved as a non-Newtonian shear thinning liquid at a specific temperature and with a specific ratio of water and propylene glycol. In another paper, Vallejo et al [12] investigated the the rheological properties of six carbon-based nonliquids. An ethylene glycol-based Si 3 N 4 nanofluid was experimentally studied byŻyła et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies have reported low shear rate viscosity profiles of WBDF by adding nanocomposites. For instance, Vallejo et al [ 69 , 70 ] conducted studies of loaded dispersions of carbon black (0.25%), nano-diamonds (0.50%), graphite/diamond (1%), and graphene nanoplates (1.5%) to analyze shear rates of 24 nanofluids. By increasing temperature, the samples presented a decrease in viscosity of 76% to 84% at a shear rate of 57.4 s −1 and 79% to 83% at a shear rate of 489 s −1 .…”
Section: Variation Of Rheological Properties By Nanocompositesmentioning
confidence: 99%